An autoethnographic exploration of higher education curriculum evaluation in Africa: implications for the education system - Mensah Prince Osiesi; Sylvan Blignaut; Muki SF Moeng; Monica Ngozi Odinko (SAPIENTIAE)
Despite the importance of the curriculum to societal development and well-being, very little attention has been given to curriculum evaluation vis-a-vis the strategies and impact on the African society/higher education system. Being a qualitative ethnographic study, this study explored the reflections of four higher education academics on the essence of and impact of curriculum evaluation on the African society, as well as the strategies for higher education curriculum evaluation. The study is collaborative autoethnographic research. The purposive sampling technique was used to select four experienced academics from higher education institutions in Nigeria and South Africa. The researchers were the data collection tools. Results were reflectively and critically analyzed and collated using a dedicated WhatsApp platform. Verbatim reporting was utilized to report the study’s findings. Findings reveal that evaluating the higher education curriculum avails of it with the expectation of what a curriculum should be, as well as meeting global standards, competitiveness, and societal needs; curriculum evaluation does necessitate positive transformation on the general standard of education; and strategies for its evaluation are diverse and context oriented. For a higher education curriculum to meet the expectations of the 21st century, its evaluation should be regularly and collectively carried out by education players and actors. The challenges impeding effective and regular evaluation of the higher education curriculum in Africa should be urgently addressed.